Evaluation of bacterial interference and beta-lactamase production in management of experimental infection with group A beta-hemolytic streptococci. - Brook, I (1993)
The in vivo effects of penicillin and cefprozil therapy on the interaction between organisms commonly recovered from inflamed tonsils were studied by using a subcutaneous abscess model in mice. These organisms were group A beta-hemolytic streptococci (GABHS), Streptococcus salivarius (which is capable of interfering with GABHS), and Staphylococcus aureus. In mice infected with GABHS and S. salivarius alone or in combination, penicillin eliminated both organisms and cefprozil eliminated GABHS and S. aureus but not S. salivarius. Penicillin did not, however, reduce the number of GABHS or S. salivarius in the presence of S. aureus. The present study demonstrated the ability of beta-lactamase-producing S. aureus to protect GABHS from penicillin. However, no such protection was present following the administration of cefprozil. Furthermore, the preservation of S. salivarius that interferes with GABHS growth may provide protection from reinfection with GABHS. This study supports and provides an explanation for the increased efficacies of cephalosporins administered orally over that of penicillin when treating patients with acute GABHS pharyngitis or tonsillitis.